The origin of the gods : a psychoanalytic study of Greek theogonic myth - Caldwell, Richard S. (Oxford University Press, 1993)
This innovative study posits that myths in general, and Greek theogonic myth in particular, have a latent meaning that is responsible both for the emotional energy inherent in myths, and for the special attraction they have even to those who no longer believe in their literal meaning. Caldwell describes, in clear and comprehensible language, aspects of psychoanalytic theory relevant to the understanding of Greek myth, implementing a psychoanalytic methodology to interpret the Greek myth of origin and succession, particularly as stated in Hesiod's Theogony. In reassessing this work, which tells the story of the world's beginning from unbounded Chaos to the defeat of the Titans, Caldwell addresses several unexplained problems-- why does the world begin with the spontaneous emergence of four uncaused entities, and why in this particular order? Why does Ouranos prevent his children from being born by confining them in their mother's body? Why is Ouranos castrated by his son, and why is Aphrodite born from the severed genitals? Why is it always the youngest son who overthrows his father, the sky-god, and what is the logic of the steps taken by Zeus to prevent the same thing happening to him? Presenting a new definition and analyses of the psychological functions in myth, this new study should appeal to a wide range of classicists, teachers and students of mythology, and those interested in the application of psychoanalytic methods to literature.